Isolation and identification of mycorrhizal fungus from an epiphytic orchid (Rhynchostylis retusa L. Bl.) - Bhuiyan, MS; Hossain, MM; Hossain, Kazi Shakhawath; Islam, Mohammad Nurul (Bangladesh Journal of Botany, 2021)
Isolation and identification of mycorrhizal fungi from the roots of Rhynchostylis retusa indicated that the cultural and microscopic features, namely colony appearance, colony colour, diameter of vegetative hyphae, presence of monilioid cells, right angle branching pattern of the fungal endophyte corroborated the identity of the fungus Rhizoctonia like anamorphs of Ceratobasidium species. Fungal identity was further confirmed through sequencing and analysis of internal transcribed spacer (ITS) sequences of the nuclear ribosomal DNA (nrDNA). ITS sequence of the isolate RhY10A6 (accession no. MN120903.1) showed > 99% similarity with several isolates of the teleomorphic fungus Ceratobasidium sp. in NCBI mega blast search. The phylogenetic analysis based on maximum parsimony method, this orchid mycorrhizal fungus clustered with several isolates of Ceratobasidium sp. or Rhizoctonia like fungi. It showed near distant relation with Ceratobasidium ramicola (GeneBank accession no. NR_138368.1) which is an orchid mycorrhizal fungus. Therefore, molecular characterization validated the morphological data. The techniques established in this orchid will facilitate to isolate and accurate identification of mycorrhizal fungus.